Interrogating the 'Germanic' a category and its use in Late Antiquity and the Early Middle Ages - Interrogating the "Germanic": a category and its use in Late Antiquity and the Early Middle Ages; Friedrich, Matthias 1988-; Harland, James M.; Walter de Gruyter GmbH & Co. KG (Ergänzungsbände zum Reallexikon der germanischen Altertumskunde, 2021)
Frontmatter -- Contents -- List of Contributors -- Introduction: The 'Germanic' and its Discontents -- The Marriage of Philology and Race: Constructing the 'Germanic' -- Rome and Its Created Northerners -- Re-inventing the 'Germanic' in the Early Modern Era: Omnes Germani sunt, contra fabulas quorundam -- The Balloon that Wouldn't Burst: A Genealogy of 'Germanic' -- What Can Cultural Anthropology Do for Medievalists? A Methodological Discussion of Ethnicity Applied to Late Antique and Early Medieval History -- From Rhetoric to Dialectic: The Becoming 'Germanic' of Visigothic (Legal-)Literature, and (Postulating) the End of a 'Truth' -- Sidonius Apollinaris's Use of the Term Barbarus: An Introduction -- A Habitus Barbarus in Sub-Roman Britain? -- A Farewell to Arms: Germanic Identity in Fifth-Century Britain -- Germanic or Slavic? Reconstructing the Transition from Late Antiquity to the Early Middle Ages in East Central Europe -- Linguistic Labels and Ethnic Identity -- (Proto-)Germanic Alliterative Verse: Linguistic Limits on a Cultural Phenomenon -- The Limits of Obligation and Friendship: Hrothgar, Beowulf, and the 'Germanic' Ideal -- Index